2012
DOI: 10.1111/j.1551-2916.2012.05210.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ceramic/Camphene‐Based Co‐Extrusion for Highly Aligned Porous Alumina Ceramic Tubes

Abstract: We herein propose a novel way of producing highly aligned porous alumina tubes by co‐extruding an initial feed rod, which comprised of a pure camphene core and a frozen alumina/camphene shell. This new and simple technique produced alumina tubes (~4.4 ± 0.1 mm in outer diameter) having uniform alumina walls (~1.1 ± 0.12 mm in thickness) with highly aligned pores, which were created by removing the extensively elongated camphene dendrites in the extruded alumina/camphene shell. Furthermore, the heat treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…As the initial alumina content increased from 15 to 25 vol%, the overall porosity of the samples, calculated from their dimensions and weight, decreased from 84 ± 1.0 vol% to 68 ± 4.3 vol%. This was mainly attributed to a decrease in the porosity of the alumina walls, as is often the case with porous ceramics produced using freeze casting . The porosity of the alumina walls, which was roughly calculated by considering the overall porosity of the samples and the fraction of the macrochannels, decreased from 76 to 57 vol% with an increase in initial alumina content from 15 to 25 vol%.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…As the initial alumina content increased from 15 to 25 vol%, the overall porosity of the samples, calculated from their dimensions and weight, decreased from 84 ± 1.0 vol% to 68 ± 4.3 vol%. This was mainly attributed to a decrease in the porosity of the alumina walls, as is often the case with porous ceramics produced using freeze casting . The porosity of the alumina walls, which was roughly calculated by considering the overall porosity of the samples and the fraction of the macrochannels, decreased from 76 to 57 vol% with an increase in initial alumina content from 15 to 25 vol%.…”
Section: Resultsmentioning
confidence: 95%
“…This was mainly attributed to a decrease in the porosity of the alumina walls, as is often the case with porous ceramics produced using freeze casting. 12,14 The porosity of the alumina walls, which was roughly calculated by considering the overall porosity of the samples and the fraction of the macrochannels, decreased from 76 to 57 vol% with an increase in initial alumina content from 15 to 25 vol%. However, regardless of the initial alumina contents, all the samples showed that a commercial epoxy could completely infiltrate into the pores (data not shown here), suggesting good interconnection between the pores.…”
Section: Resultsmentioning
confidence: 99%
“…[ 107 ] However, the formation of aligned micro pores is limited in this approach. Highly oriented pores can be obtained by a 3D ceramic/camphene‐based coextrusion (3D‐CoEx) technique ( Figure A), [ 108 ] in which a continuous ceramic/camphene filament consisting of a pure camphene core and a frozen alumina/camphene shell is deposited by coextrusion. Subsequently, unidirectional macrochannels and interconnected micropores are created through removal of camphene.…”
Section: Freeze Casting Materials In New Geometriesmentioning
confidence: 99%
“…Reproduced with permission. [ 108c ] Copyright 2015, Elsevier. B) Schematic of 3D printing combining freeze casting and extrusion/inkjet.…”
Section: Freeze Casting Materials In New Geometriesmentioning
confidence: 99%
“…However, the difficulties demolding the tubes after solidification is drawback of this set-up that limits further industrial development. Moon et al [27] overcomes this issue combining ice-templating with co-extrusion, however the resultant porosity is not radially aligned.…”
mentioning
confidence: 99%